KENDALI GEOLOGI TERHADAP POLA ALIRAN AIRTANAH BEBAS DAN TERKEKANG DALAM EVALUASI POTENSI AKIFER, STUDI KASUS DAERAH PANDAAN DAN SEKITARNYA, KABUPATEN PASURUAN, JAWA TIMUR - Reza, Teuku; Hendarmawan, .; Alam, Boy Yoseph Cahya Sunan Sakti Syah (Bulletin of Scientific Contribution, 2020)
Geological control has been examined on the pattern of groundwater flow from free and confined aquifer in the evaluation of aquifer potency in case study in the Pandaan and surrounding areas, Pasuruan Regency, East Java. Groundwater elevation (MAT) measurement data of dug wells, borehole pumping tests, 1D geoelectricity, and wellbore log results indicate that groundwater flow patterns from free and confined aquifers have the same flow direction from southwest to northeast indicating that the distribution hydrogeological units of both aquifers are relatively homogeneous. The depths of the free aquifer from 1 to 6 meters with sand and tuffaceous sand lithology. Confined aquifer from a depth of 40 meters with a thickness between 20 to 70 meters. The aquifer unit is a tuff breccias rock from the Mt. Arjuna Welirang and Tuf Rabano Formation, aquiclude units in the form of andesite lava from Mt. Arjuna Welirang. Potential confined aquifer evaluated from pumping test has a transmissivity value between 54 - 315 m2 / day. Hydraulic conductivity (k) values are between 1.46 - 12.4 m / day. Keywords: Hydrogeological unit, transmissivity, hydraulic conductivity, aquifer, aquiclude